Jeszcze o rutenizmach we współczesnym polskim języku ogólnym w ujęciu Andrzeja Bańkowskiego - Fałowski, Adam (Slavia Orientalis, 2026)
This article discusses 79 lexical units classified as potential ruthenisms in contemporary Polish in A. Bańkowski’s Etymological Dictionary of the Polish Language. A detailed and comprehensive formal, chronological, geographical, and semantic-stylistic analysis of these lexemes shows that only a small fraction (12 units) can be considered more or less likely ruthenisms. These include: chwacki, chwat, cudotwórca, kabała ‘difficult situation, trouble, problem’, kuc, kuksać, podmówić, podpowiadać (calque), polubowny, prawowierny, przerodzić (się), przywidzieć się. The remaining ones are: 1) formations of native Polish origin (48), 2) words adopted from languages other than East Slavic (1), 3) Russianisms (6), 4) words that do not lend themselves to unambiguous etymological interpretation (12).